The effects of high-intensity functional training on aerobic capacity, metabolic adaptation and neuromuscular responses in young female volleyball players - BOZDOĞAN, TUBA (My University, 2021)
The aim of the study is to evaluate the effects of High Intensity Functional Training (HIFT) program on aerobic capacity, metabolic adaptation and neuromuscular responses in young female volleyball players. 22 licensed female athletes (16.41±1.29 years old) who played volleyball actively for at least two years in the regional women\"s volleyball league voluntarily participated in the study. Participants were divided into two groups as experimental (EG; n=11) and control group (CG; n=11) by random sampling method. CG only participated in routine volleyball training for 12 weeks. CG only participated in routine volleyball training for 12 weeks. In addition to volleyball training, EG participated in the 12-week HIFT program, which included sprinting, plyometric, functional body weight, resistance and aerobic exercises two days in a week. Measurements were taken before and after the training program as pre-test and post-test. Anthropometric measurements (height, body weight, body fat percentage, body mass index) of the participants were taken. Metabolic (Lactate) and aerobic capacity measurement (Maximum oxygen consumption (VO2max) of the participants were taken with the Yo-yo Intermittent Recovery (level-1) Test protocol. Moreover, neuromuscular tests (Counter Movement Jump (CMJ) and 10x20m repetitive sprint fatigue index) were applied. Statistical analysis of the data obtained was done using the SPSS 22.0 statistical package program. As a result of the study, a statistically significant difference was observed in the CMJ and Yo-yo Intermittent Recovery (level-1) Test in CG, and in the CMJ, 10x20m repetitive sprint fatigue index, Yo-yo Intermittent Recovery (level-1) and VO2max tests in EG at the end of 12-week HIFT program (p<0.05). In addition, when EG and CG were compared, it was determined that there was a statistically significant difference in the favor of EG between the CMJ test and 10x20m repetitive sprint fatigue index post-test mean values (p<0.05). As a conclusion, it can be said that 12-week HIFT is a training method that can positively affects the aerobic capacity, jump force and neuromuscular responses of young female volleyball players. Therefore, HIFT can be used to improve the performance of young female volleyball players and added to their annual training regimen.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; HIFT; Volleyball; Athletic Performance; CMJ; Repeated Sprint; VO2max